Coaching 5.0, coaching for the fifth industrial revolution - Rasool, Jazz (Frontiers in Virtual Reality, 2025)
The rising use of Artificial Intelligence (AI), Metaverse and Blockchain technologies has influenced capabilities in a wide variety of industries. These have now started to provide affordances for automating provision of insight and empowerment in coaching business leaders and staff. This paper discusses the risk, that as such technologies become smarter, human beings may abdicate their thinking capabilities, especially related to creative problem solving, to machine intelligence. The author calls for prevention of cognitive decline in human beings as machines get smarter. A route to this can be mapped through use of Industry 5.0, Fifth Industrial Revolution (5IR) approaches, that focus on a harmonisation of human and machine intelligence, ensuring human beings can make machines smarter and that machine intelligence can in turn make human consciousness advance. Practitioner Coaches, to future proof their practice, must ensure they embody 5IR mindsets, techniques and technologies. The coaching discipline that is fit for practice in 5IR environments and contexts is what the author has called “Coaching 5.0.” This paper looks at Coaching 5.0 components and how they can be adopted by coaches to ensure the future is sustainable, insightful and empowering one for their practice and for their clients.